Writing for news media : the storyteller's craft - Pickering, Ian (London ; New York : Routledge, 2018)
'Writing for News Media is a down-to-earth guide on how to write news stories for online, print and broadcast audiences. It celebrates the craft of storytelling, arguing for its continued importance in a modern newsroom. With dynamism and humour, Ian Pickering, a journalist with 30 years' experience, offers readers practical advice on being a news journalist, with step-by-step guidance on creating a great story and writing the perfect news copy. Chapters include: - extracts from published news articles to help illustrate the dos and don'ts of storytelling; - the ten golden rules for putting together a successful news article, including 2. Know your audience, 3. Nail the intro, 6. Keep it simple and 9. Knock out the niggles; - instruction on writing stories for different specialist subjects, including politics, court cases, economics, funnies and celebrity; - help for readers on how to write for broadcast news journalism; - tips on how to avoid common style and grammar mistakes, with a special section on using quotations; - glossaries covering a range of different aspects of news journalism, like online media, types of news story, typesetting and broadcasting. This is an instructive and insightful manual which champions brilliant writing and an exemplary use of English. It introduces a set of key creative and analytical techniques that will help students of journalism and young professionals hone and refine their story writing skills' --
You, the storygatherer -- What is news? -- Tools of the trade -- Borrow from bond -- Building a story -- The first golden rule -- The other golden rules -- Headlines, quotes and pictures -- Tackling different subjects -- Broadcast -- The non-rules of grammar.
Includes bibliographical references and index.
Keywords: Journalism -- Authorship; Storytelling in mass media; Television broadcasting of news -- Handbooks, manuals, etc